2011
DOI: 10.1109/tase.2010.2102351
|View full text |Cite
|
Sign up to set email alerts
|

A Convex Optimization Framework for Almost Budget Balanced Allocation of a Divisible Good

Abstract: Abstract-We address the problem of allocating a single divisible good to a number of agents. The agents have concave valuation functions parameterized by a scalar type. The agents report only the type. The goal is to find allocatively efficient, strategy proof, nearly budget balanced mechanisms within the Groves class. Near budget balance is attained by returning as much of the received payments as rebates to agents. Two performance criteria are of interest: the maximum ratio of budget surplus to efficient sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…We therefore adopt Moulin's proposal of minimizing (9). Chorppath et al [5] studied exactly this proposal in the divisible goods setting, but in the simpler restricted VCG setting of footnote 3. While the Moulin proposal is defensible for that setting, it has the drawback in our SSVCG setting that σ(θ) is not known to the social planner.…”
Section: Design For the Worst Casementioning
confidence: 99%
See 3 more Smart Citations
“…We therefore adopt Moulin's proposal of minimizing (9). Chorppath et al [5] studied exactly this proposal in the divisible goods setting, but in the simpler restricted VCG setting of footnote 3. While the Moulin proposal is defensible for that setting, it has the drawback in our SSVCG setting that σ(θ) is not known to the social planner.…”
Section: Design For the Worst Casementioning
confidence: 99%
“…where (15) is the same as (4), and (16) is the same as (6). This choice puts us in the optimization framework of Chorppath et al [5], except that we have not yet shown how to resolve the issue of dependence of (16) on the private information v i . We now highlight two important differences between our work and that of Yang and Hajek [25].…”
Section: Design For the Worst Casementioning
confidence: 99%
See 2 more Smart Citations
“…Consider an auction mechanism in the context of a wireless network and uplink power control setting [22,25] where due to the interference coupling the resource sharing is inherently competitive. Let the user utilities be taken as U i (γ i (Q(x)) and the individual power levels,…”
Section: Interference-coupled Systems (Cdma Power Control)mentioning
confidence: 99%